Extension of earth orbits using low-thrust propulsion - Anderson, Pamela; Macdonald, M. (2010)
The primary motivation for the utilization of space for environmental science, and in-particular Earth Observation, is the unique vantage point which a spacecraft can provide. For example, a spacecraft can provide a global dataset with a much higher temporal resolution than any other platform. Earth Observation spacecraft are increasingly focused on a single primary application, typically conducted from a small set of classical orbits which limits the range of vantage points and hence the type of observations which can be made. The next generation of innovative Earth Observation spacecraft may however only be enabled through new orbit options not considered in the past. The objective of the study was therefore to enlarge the set of potential Earth orbits by considering the use of low-thrust propulsion to extend the conventional Molniya orbit. These new orbits will use existing, or near-term low-thrust propulsion technology to enable new Earth Observation science and offer a radically new set of tools for mission design. Continuous low-thrust propulsion was applied in the radial, transverse and normal directions to vary the critical inclination of the Molniya orbit, while maintaining the zero change in argument of perigee condition. As such the inclination can be freely altered from the expected critical inclination of 63.4 deg, to, for example 90 deg, creating a Polar-Molniya orbit. Analytical expressions were developed which were then validated using a numerical model, to show that not only was the argument of perigee unchanged but all other orbital elements were also unaffected by the applied low-thrust. It was shown that thrusting in the transverse direction allowed the spacecraft to achieve any inclination with the lowest thrust magnitude in any single direction; this value was however found to be further reduced by combining both radial and transverse thrust. Real-time continuous observation of the Arctic Circle is then enabled using current electric propulsion technology, with fewer spacecraft than the ...